DEVELOPMENT OF AN APPLICATION FOR REMOVABLE PARTIAL DENTURE PLANNING THROUGH SMARTPHONES: PROSTHESIS PLAN (REMUNOM, 2026)
Oral rehabilitation with removable partial dentures aims to restore masticatory function, aesthetics, and patients' quality of life. With advancements in Digital Dentistry, the proposal emerged to develop Prótese Plan, an application focused on the digital planning of removable partial dentures, created to facilitate the work of dental surgeons, students, and technicians, enhancing precision, efficiency, and communication. The study followed the Contextualized Instructional Design (CID) model, encompassing needs analysis, technology review, interactive screen design, development using React Native and Typescript, and implementation for free distribution. The application features a user-friendly interface in shades of lilac and blue, with six navigable screens, including patient registration, dental arch manipulation, and prosthetic planning design. It is compatible with Android devices starting from 2GB of RAM and 100MB of storage, ensuring adequate accessibility. Prótese Plan stands as an innovative tool that contributes to rehabilitative planning, education, and clinical practice in Dentistry, adapting to different therapeutic approaches and favoring communication between professionals.